The Influence of Psychological Factors on The Buying Decision Process of Tropicana Slim Sweetener Products - Rahayu, Gita; Kurniati, Dewi; Suharyani, Anita (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 14 No 2 (2020): Vol.14.No 2, 2020DO - 10.24843/SOCA.2020.v14.i02.p06, 2020)
This research aimed to determine the influence of psychological factors on buying decisions of Tropicana Slim Sweetener products. This research was conducted in Pontianak, West Kalimantan Province. The psychological factors of consumers in making the buying decision process consisted of motivation, perception, learning, beliefs and attitudes. The population used in this research was consumers of Tropicana Slim Sweetener. The sample used was 150 people, using purposive sampling. The research was conducted in June to July 2018. The research data were obtained by the analysis method using Structural Equation Modeling (SEM). The results showed that psychological factors had a positive influence on consumer buying decisions, with the most influenced indicators were convince in the product, belief in the product, product brand, knowledge of the product, the feelings towards the product and product reliability.